Registration of #STRKR Barley Germplasm. Issue 3 (17th April 2015) - Meints, Brigid; Brouwer, Brook O.; Brown, Bradford; Cuesta-Marcos, Alfonso; Jones, Stephen S.; Kolding, Mathias; Fisk, Scott; Marshall, Juliet M.; Murphy, Kevin; Petrie, Steven; Rhinhart, Karl; Ross, Andrew S.; et al.
Abstract : #STRKR (Reg. No. GP‐208, PI 674325) is a hulless, six‐row barley ( Hordeum vulgare L.) germplasm composed of the bulk of three full‐sib lines, two of which have winter growth habit and one of which has facultative growth habit. The germplasm was released by the Oregon Agricultural Experiment Station in 2014. The three sister lines from the Oregon State University Barley Breeding Program that were bulked to form #STRKR were derived from the cross of F1 ('Maja'/'Legacy')/Maja/3/'Doyce'. #STRKR was tested under the experimental designation Streaker. The #STRKR germplasm is uniform for spike type, rachilla hair length, resistance to stripe rust (incited by by Puccinia striiformis f. sp. hordei ), and grain quality parameters. It is relatively uniform in terms of height and heading date. #STRKR is phenotypically heterogeneous for awn texture, grain color, and tolerance to scald (incited by Rhynchosporium commune ). As a blend, #STRKR has shown winter survival comparable to Maja in environments where there was differential winter injury. #STRKR germplasm provides a resource for reselection and a parental source for disease resistance and quality parameters.